KEPEMIMPINAN KEPALA MADRASAH DALAM PENGUATAN MODERASI BERAGAMA: SEBUAH SYSTEMATIC LITERATURE REVIEW - Qolbi Alif Ridlollah; Syeh Al Ngarifin; Muhtarom Muhtarom; Abdul Hamid (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Religious moderation is one of the national priority agendas proclaimed by the Ministry of Religious Affairs of the Republic of Indonesia, particularly in the context of Islamic education. Madrasa principals, as leaders of Islamic educational institutions, play a key role in creating a moderate, tolerant, and inclusive learning environment. However, studies that systematically map the role of madrasa principal leadership in the context of strengthening religious moderation remain very limited. This article aims to fill this gap through a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. From 187 articles found through searches in various scientific databases, 25 articles were selected based on predetermined inclusion and exclusion criteria. Thematic analysis results indicate three main findings: first, effective madrasa principals implementing religious moderation generally apply a value-oriented transformational leadership approach; second, there are a number of supporting and inhibiting factors that consistently appear in various madrasa contexts in Indonesia; and third, strong madrasa principal leadership is proven to positively correlate with the formation of a moderate and inclusive madrasa culture. These findings are expected to serve as a reference for madrasa principals, policymakers, and future researchers in strengthening religious moderation in Islamic educational institutions. ABSTRAK Moderasi beragama merupakan salah satu agenda prioritas nasional yang dicanangkan Kementerian Agama Republik Indonesia, khususnya dalam konteks pendidikan Islam. Kepala madrasah, sebagai pemimpin lembaga pendidikan Islam, memegang peranan kunci dalam mewujudkan lingkungan belajar yang moderat, toleran, dan inklusif. Namun demikian, kajian yang secara sistematis memetakan peran kepemimpinan kepala madrasah dalam konteks penguatan moderasi beragama masih sangat terbatas. Artikel ini bertujuan untuk mengisi kesenjangan tersebut melalui pendekatan Systematic Literature Review (SLR) dengan mengikuti panduan PRISMA 2020. Dari 187 artikel yang ditemukan melalui penelusuran di berbagai database ilmiah, sebanyak 25 artikel dipilih berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Hasil analisis tematik menunjukkan tiga temuan utama: pertama, kepala madrasah yang efektif mengimplementasikan moderasi beragama umumnya menerapkan pendekatan kepemimpinan transformasional yang berorientasi nilai; kedua, terdapat sejumlah faktor pendukung dan penghambat yang secara konsisten muncul dalam berbagai konteks madrasah di Indonesia; dan ketiga, kepemimpinan kepala madrasah yang kuat terbukti berkorelasi positif dengan terbentuknya budaya madrasah yang moderat dan inklusif. Temuan ini diharapkan dapat menjadi rujukan bagi kepala madrasah, pengambil kebijakan, dan peneliti selanjutnya dalam upaya memperkuat moderasi beragama di lembaga pendidikan Islam.